PENGARUH KONFLIK PERAN DAN STRES KERJA TERHADAP KINERJA KARYAWAN: STUDI PADA KARYAWAN PT GLORY INDUSTRIAL SEMARANG II DI SEMARANG - Astono, Ari Dwi; Ristanto, Hesti; Haryanik, Dwi (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2019)
The purpose of this study was to find out and analyze the influence of role conflict and work stress on employee performance, the population in this study were employees of the sewing department of PT Glory Industrial Semarang II, the study respondents consisted of 96 employees. Research data obtained from the results of questionnaires. The equation model is processed with the SPSS application, the results of the study can be concluded that: a) Role conflict positive and non-significant effect on employee performance, b) Job stress has a positive and significant effect on employee performance, c) Simultaneous role and work stress conflict have a significant effect on employee performance.